The Moment Study: protocol for a mixed method observational cohort study of the Alternative Nicotine Delivery Systems (ANDS) initiation process among adult cigarette smokers. Issue 4 (22nd April 2016) - Pearson, Jennifer L; Smiley, Sabrina L; Rubin, Leslie F; Anesetti-Rothermel, Andrew; Elmasry, Hoda; Davis, Megan; DeAtley, Teresa; Harvey, Emily; Kirchner, Thomas; Abrams, David B
Abstract : Introduction: Alternative Nicotine Delivery Systems (ANDS) such as e-cigarettes are battery-powered devices that aerosolize nicotine and other substances to simulate smoking without using tobacco. Little is known about the ANDS initiation process among adult smokers. The aims of this research are threefold to: (1) examine how ANDS use affects cigarette use; (2) examine how the immediate environmental and psychosocial contexts of cigarette and ANDS use vary within—and between—participants in general and by menthol preference and race; and, (3) examine participants' 'lived experience' of the subjective perceptions, meaning, influences and utility of cigarette and ANDS use. Methods and analyses: This study's mixed method, 6-week longitudinal design will produce a detailed description of the ANDS initiation process among adult smokers (N=100). Qualitative and quantitative data collection will include 3 weeks of: (1) ecological momentary assessment of patterns of cigarette/ANDS use, satisfaction, mood and craving; (2) geospatial assessment of participants' environment, including indoor and outdoor cigarette/ANDS norms and rules; (3) in-depth interviews about the meaning and utility of cigarette smoking and ANDS use; and, (4) saliva cotinine and exhaled carbon monoxide (CO) biomarkers. A diverse sample will be recruited with an equal number of menthol and non-menthol cigarette smokers. As the primary independent variable, we will investigate how ANDS use affects cigarette consumption. We will also examine how smoking-related and ANDS-related rules and norms surrounding product use influence cigarette and ANDS product use, and how the subjective effects of ANDS use affect ANDS perceptions, beliefs and use. Ethics and dissemination: This study was funded by the National Institute on Drug Abuse of the US National Institutes of Health (1R21DA036472), registered at ClinicalTrials.gov (NCT02261363 ), and approved by the Chesapeake IRB (Pro00008526). Findings will be disseminated to the scientific and lay community through presentations, reports and scientific publications. Trial registration number: NCT02261363; Pre-results.